The Effects of COVID-19 information sources and knowledge, attitude, and behaviour on vaccination acceptance - Rivaldo Steven Heriyanto; Theo Audi Yanto; Gilbert Sterling Octavius; Haviza Nisa; Catherine Ienawi; H. Emildan Pasai (Journal of Community Empowerment for Health, 2023)
This study aimed to assess the impact of COVID-19 information-related sources and people’s knowledge, attitude, and behavior concerning vaccine acceptance, hesitancy, and refusal in a single vaccination site in Jambi, Indonesia. We conducted a cross-sectional study with total sampling in Puskesmas Putri Ayu, Jambi. The inclusion criteria were adults (>18 years) vaccinated with CoronaVac. Our exclusion criteria were refusal to participate in the study for any reason, contraindicated to COVID-19 vaccine administration, and receiving the second vaccine jab. We included 245 respondents with a slight female predominance (53.5%). The majority were in the age group of 26-35 years old (20.8%). In the multivariate analysis, having a family member with ≥2 comorbidities was almost 6 times more likely (OR 5.99, 95%CI: 1.84-19.54;p-value = 0.003) to put a respondent in the vaccine hesitance and refusal group. Respondents who trust in friends or family are 2.25 times more likely (95%CI: 1-5.04; p-value = 0.048) to be in the vaccine hesitance and refusal group. Respondents who trust the internet are 0.45 times more likely to be in the vaccine hesitance and refusal group (95%CI: 0.21-0.96; p-value = 0.04). Lastly, respondents with poor knowledge are 0.58 times more likely (95%CI 0.38-0.88; p-value = 0.011) to belong to the vaccine hesitance and refusal group. This finding will be relevant to increasing vaccination uptake by targeting family members with comorbidities and devising a strategy to make their peers trust the COVID-19 vaccine to increase the uptake.